Academic Self-Regulation, Chronotype and Personality in University Students During the Remote Learning Phase due to COVID-19 - Staller, Naomi; Großmann, Nadine; Eckes, Alexander; Wilde, Matthias; Müller, Florian H.; Randler, Christoph (Frontiers in Education, 2021)
During the COVID-19 shutdown phase in Germany, universities stopped presence teaching and students had to turn to digital instruction. In order to examine their capability to cope with the changed learning situation, we assessed how basic psychological need satisfaction and frustration, motivational regulation, vitality and self-efficacy of 230 German university students (74% female) relate to their chronotype and personality (Big Five). Specifically, we were interested in whether chronotype and personality dimensions are predictors for successful remote learning. Since the pandemic and remote learning will accompany teaching and learning at university in 2021, predictors of successful remote learning need to be identified in order to support student learning optimally in digital learning environments. In our study, morning-oriented, conscientious, and open students with low neuroticism seem to better cope with the shutdown environment due to vitality, self-efficacy, and partly their self-determined motivation. Moreover, our findings indicate that students need different support depending on their chronotype and personality during the digital learning phase.